PENINGKATAN PRODUKSI UNGGAS MELALUI MANAJEMEN PERKANDANGAN, KESEHATAN TERNAK, DAN MANAJEMEN PENETASAN YANG BAIK - Fitasari, Eka (Jurnal Difusi Ipteks Legowo, 2023)
Animal husbandry and agriculture are vital sectors of the community's economy that can run in synergy and support each other. Currently, independent livestock is a form of community effort that can survive global competition and contribute to food security, especially during the COVID-19 pandemic. However, there is a problem faced by farmers or breeders is that they have not been able to process existing vegetable waste and manage farms according to maintenance standards, so that the livestock population tends not to grow rapidly. The form of the solution that is offered is through a comprehensive management improvement from tillers to livestock products. Activities that have been carried out are implementing housing management through improving livestock sheds, implementing biosecurity practices, and handling poultry health, fulfilling livestock nutrition, making pellets using machines, as well as introducing technology for making pellet feed based on vegetable waste from farmers, and improving reproduction through crossing and Automatic Hatching Machine. The results of this activity are the improvement of livestock health, the production of vegetable waste-based poultry pellets to reduce feed costs and can be stored for a long time, and an increase in hatchability of more than 80%. The impact of the results of community service activities is an increase in livestock populations and the creation of a healthy veterinary environment.